2001
DOI: 10.1128/aem.67.5.2367-2370.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the csgD Promoter Associated with Variations in Curli Expression in Certain Strains of Escherichia coli O157:H7

Abstract: Single-base-pair csgD promoter mutations in human outbreak Escherichia coli O157:H7 strains ATCC 43894 and ATCC 43895 coincided with differential Congo red dye binding from curli fiber expression. Red phenotype csgD::lacZ promoter fusions had fourfold-greater expression than white promoter fusions. Cloning the red variant csgDEFG operon into white variants induced the red phenotype. Substrate utilization differed between red and white variants.Many Escherichia coli organisms and salmonellae express coiled surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
123
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 18 publications
9
123
1
1
Order By: Relevance
“…For Sarc16, the change was in the Ϫ35 region and shifted the PagfD sequence closer to the 70 consensus (39). In E. coli, enhanced Tafi (curli) production has been linked to PagfD (PcsgD) mutations in the Ϫ10 region that move the sequence closer to the 70 consensus (62). The changes that occurred in Sarc4 and Sarc16 were also predicted to allow for 70 -based transcription of agfD.…”
Section: Discussionmentioning
confidence: 99%
“…For Sarc16, the change was in the Ϫ35 region and shifted the PagfD sequence closer to the 70 consensus (39). In E. coli, enhanced Tafi (curli) production has been linked to PagfD (PcsgD) mutations in the Ϫ10 region that move the sequence closer to the 70 consensus (62). The changes that occurred in Sarc4 and Sarc16 were also predicted to allow for 70 -based transcription of agfD.…”
Section: Discussionmentioning
confidence: 99%
“…(40,49). Both genera have curli genes; however, it has been reported that single-base-pair csgD promoter mutations leave Ն95% of E. coli O157:H7 cells unable to express curli (47). These mutations also cause E. coli O157:H7 to display increased virulence in mice and increased invasion of HEp-2 cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…coli O157:H7 expresses multiple fimbrial and nonfimbrial adhesins which have no obvious role in pathogenesis and may be involved in adhesion to other surfaces (reviewed in reference 46). For example, curli-expressing thin aggregative fim-briae, which are rarely reported in E. coli O157:H7 compared with other pathogenic E. coli strains (47,48), have been reported to bind eukaryotic extracellular matrix proteins as well as to enhance the formation of E. coli O157:H7 biofilms on inert surfaces (11,38). Biofilm formation may increase E. coli O157:H7 survival and would likely result in protection against many environmental conditions.…”
mentioning
confidence: 99%
“…In contrast, enteroinvasive E. coli (EIEC), Shigella spp. and enterohaemorrhagic E. coli (EHEC) regularly do not express curli fimbriae in vitro (Bian et al, 2000;Cookson et al, 2002;Patri et al, 2000;Sakellaris et al, 2000;Sjöbring et al, 1994;Uhlich et al, 2001).…”
Section: Introductionmentioning
confidence: 99%